2017
DOI: 10.1371/journal.pone.0188945
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum cytokines, chemokines, growth factors and enzymes with periodontal disease parameters

Abstract: BackgroundPeriodontal disease (PD) is characterized by inflammatory tissue destruction in tooth supporting apparatus. Many studies indicate that the underlying pathogenesis is in concordance with rheumatoid arthritis (RA) sharing immune-inflammatory events affect both diseases. The aim of this study was to investigate serum cytokines, chemokines, growth factors, enzymes and costimulatory proteins in association with periodontal conditions in PD and RA subjects.Materials & methodsPeriodontal examination was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…CXCL10 has shown promise as a potential biomarker for the detection of periodontitis and post-therapy monitoring; however, no definite correlation has been established between CXCL10 levels in serum, saliva, and GCF with disease severity. 14 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…CXCL10 has shown promise as a potential biomarker for the detection of periodontitis and post-therapy monitoring; however, no definite correlation has been established between CXCL10 levels in serum, saliva, and GCF with disease severity. 14 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that T cell aberration and reduced levels of anti-inflammatory IL-10 are associated with severe periodontal conditions [13]. FGF-19 and FGF-21 are late-acting hormones that induce the secretion of insulin and glucagon to regulate glucose homeostasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were assayed as singletons. Methods pertaining to protein arrays, quality control, and data normalization have been discussed in detail in our previous publications [12,13].…”
Section: Proximity Extension Assay (Pea)mentioning
confidence: 99%
“…A total of thirty eight RA patients with half of them suffering from periodontal disease (15 females and four males; age range: 27 to 60 years; mean ± SD: 50.4 ± 9.1 years) and the remaining half without periodontal disease (18 females and one male; age range: 21 to 70 years; mean ± SD: 41.8 ± 13 years) were diagnosed in accordance with the 2010 ACR / EULAR Rheumatoid Arthritis Classification Criteria and recruited from the Rheumatology Clinic in Habib Medical Centre, Karachi [ 20 ]. RA disease activity was measured with the Disease Activity Score 28 joint count (DAS28) by the rheumatologist (AG) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%